(untitled) (INNOVATIVE ECONOMY, 2026)
Ivashkiv Ya.K. INCREASING THE INNOVATIVE ACTIVITY OF ENTERPRISES BASED ON COOPERATION WITH INNOVATION PARKS Purpose. The aim of the article is to study the prospects for increasing the innovative activity of enterprises based on cooperation with innovation parks. Methodology of research. The following research methods were used to achieve the set goal: theoretical generalization – to systematize research results in the field of increasing the innovative activity of enterprises based on cooperation with innovation parks; analysis and synthesis – to assess the investment attractiveness and efficiency of innovation parks, research into the dynamics of subjects-residents of the innovation park; comparison and grouping – to improve the classification of evaluation criteria and indicators used to analyse the innovative activity of enterprises; statistical analysis – to analyse the dynamics of innovatively active enterprises in Ukraine, the number of industrial enterprises that introduced innovations, and the volume of sales of innovative products; graphic – for visual presentation of analytical research results; abstract and logical – for formulating the goal, setting tasks and substantiating conclusions, which made it possible to clarify theoretical and methodological approaches in assessing the innovative activity of an enterprise and substantiate the influence of innovation parks on its increase. Findings. The theoretical provisions for ensuring the innovative development of business ecosystems in the context of strengthening the innovative activity of enterprises are disclosed. Methodological approaches to assessing the innovative activity of an enterprise are supplemented on the basis of the systematization of evaluation criteria and indicators used to analyse the innovative activity of enterprises. An analysis of innovation activity at the micro level in Ukraine in 2021–2024 was conducted according to evaluation indicators, namely: the number of innovatively active enterprises; the number of enterprises that introduced innovations and the volume of innovative products sold. Positive trends in the field of innovation activity of Ukrainian industrial enterprises were identified. The impact of innovation parks on increasing the innovative activity of Ukrainian industrial enterprises is proven. The feasibility of strengthening cooperation between enterprises and innovation parks is substantiated in order to revive the innovative activity of business ecosystems and support innovative business development in the current conditions of transformation of industrial paradigms. Originality. The substantiation of directions for increasing the innovative activity of enterprises based on cooperation with innovation parks and the clarification of evaluation criteria and indicators used to analyse the innovative activity of enterprises has been further developed Practical value. The obtained research results can be used in business development management, in particular in the formation and development of intellectual capital, improving the knowledge management system, and making management decisions in the digital economy. Key words: innovation, innovativeness, innovative activity of the enterprise, innovative activity, innovative business development, innovation parks, science parks, technology parks, business development management, digitalization.